2023
DOI: 10.1186/s11658-023-00471-8
|View full text |Cite
|
Sign up to set email alerts
|

EFEMP2 upregulates PD-L1 expression via EGFR/ERK1/2/c-Jun signaling to promote the invasion of ovarian cancer cells

Abstract: Background Fibulin-like extracellular matrix protein 2 (EFEMP2) has been reported to be related to the progression of various cancers. We have previously reported that EFEMP2 was highly expressed in ovarian cancer and was strongly associated with poor prognosis in patients. This study intends to further explore its interacting proteins and possible downstream signaling pathways. Method The expression of EFEMP2 was detected by RT-qPCR, ICC and weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“… 39 PD-L1 promoted invasion and metastasis in ovarian cancer. 40 In our study, we explored both the immune checkpoint and nonimmune checkpoint roles of PD-L1 in CRC. Functional assays have shown that knockdown of PD-L1 attenuates the proliferation, migration, and invasion of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“… 39 PD-L1 promoted invasion and metastasis in ovarian cancer. 40 In our study, we explored both the immune checkpoint and nonimmune checkpoint roles of PD-L1 in CRC. Functional assays have shown that knockdown of PD-L1 attenuates the proliferation, migration, and invasion of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…46 EFEMP2 has been reported to have implications in the advancement of different cancer types. 47 Little is known about the relationship between EFEMP2 and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…46 EFEMP2 has been reported to have implications in the advancement of different cancer types. 47 Little is known about the relationship between EFEMP2 and neurodegeneration. We found downregulation of EFEMP2 in PSP patients compared to HC and PD, and further investigation of this relationship is required.…”
Section: Discussionmentioning
confidence: 99%